Analysis of program for research and development on comprehensive prevention and control techniques for agricultural non-point source and heavy metal polluted croplands - XU Changchun; ZHENG Ge; LIN Youhua (浙江大学学报. 农业与生命科学版)
In order to improve the research and development level of prevention and control techniques for agricultural nonpoint source and heavy metal polluted croplands, a National Key R & D Program of China titled with “research and development on comprehensive prevention and control techniques for agricultural non-point source and heavy metal polluted croplands” was initiated during the 13th Five-Year Period, in the context of national research project reform. This program was designed throughout the industrial chain, including 35 research missions into three categories, such as fundamental research, common key techniques, and technique integration and demonstration. This paper introduced the backgrounds, objectives and research missions of the program, analyzed the progress and major characteristics for the research missions initiated in the years 2016 and 2017, and discussed the program management mechanism, so as to provide references for enhancing application, approval and management of National Key R & D Program of China.